STRATEGI PENGELOLAAN PEMBELAJARAN DARING DI MATLA’UL ATFAL KOTA BANDUNG - Deni indrawan; Andi Prastowo (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2022)
The purpose of this study was to obtain information about the management description of online-based learning, and the supporting and inhibiting factors of online learning at MI Matla'ul Atfal Bandung City. This research uses qualitative methods and the data analysis technique in this research is descriptive qualitative analysis. The results of the study, schools that apply online learning are seen from the management of the learning process. Shows that the role of teachers and facilities in online learning provides positive benefits for teachers and students in realizing learning objectives. The supporting factors for online learning are the facilities available in accordance with the needs and the existence of training for teachers on ICT, while the inhibiting factors are inadequate facilities, weak organization and monitoring and low internet network.keywords: Management, Online learning